Management of water resources in boi branco sub-basin -SP - Neto, Givaldo Dantas Sampaio; Bianchi, Vinícius Rafael [UNESP]; Pinto, Leonardo De Barros [UNESP]; Román, Rodrigo Máximo Sánchez [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2018)
Scarcity of water resources due to climatic factors or increase in consumption due to the intensity of some activities has generated conflicts in several regions of Brazil. Agriculture is responsible for 70% of water demand in Brazil, mainly due to the practice of irrigation. On the other hand, irrigated agriculture produces 2.7 times more than rainfed agriculture and employs on average 1.5 direct and indirect jobs per irrigated hectare. Classified in a critical situation, Boi Branco sub-basin, located in Alto Paranapanema region, Itai and Paranapanema municipalities is a strong irrigated agriculture pole. The objective of this work was to raise issues related to the management of water resources, irrigated agriculture and the participation of various sectors of water users in Boi Branco sub-basin. It was observed that quantitative and qualitative data related to water resources in the basins present inconsistency both in actual water demand and in effective availability. There is a need for greater dissemination of information on Boi Branco sub-basin together with investment in research and training of all those involved in water resources management.
Gestão dos recursos hídricos na sub-bacia hidrográfica do boi branco – Sp
Keywords: Central pivot; Irrigated agriculture; Irrigation; Water use; Watershed